Case Report and Review of the Literature: Bullous Skin Eruption After the Booster-Dose of Influenza Vaccine in a Pediatric Patient With Polymorphic Maculopapular Cutaneous Mastocytosis - Sarcina, Davide; Giovannini, Mattia; Oranges, Teresa; Barni, Simona; Pedaci, Fausto Andrea; Liccioli, Giulia; Canessa, Clementina; Sarti, Lucrezia; Lodi, Lorenzo; Filippeschi, Cesare; Azzari, Chiara; Ricci, Silvia; et al. (Frontiers in Immunology, 2021)
Vaccination is a well-known trigger for mast cells degranulation in subjects affected by mastocytosis. Nevertheless, there is no exact standardized protocol to prevent a possible reaction after a vaccine injection, especially for patients who have already presented a previous vaccine-related adverse event. For this reason, we aim to share our experience at Meyer Children's University Hospital in Florence to raise awareness on the potential risk for future vaccination and to discuss the valuable therapeutic strategies intended to prevent them, also according to what is proposed by experts in literature. We describe the case of an 18-month-old female affected by a polymorphic variant of maculopapular cutaneous mastocytosis that presented an extensive bullous cutaneous reaction 24 hours after the second dose (booster dose) of inactivated-tetravalent influenza vaccine, treated with a single dose of oral corticosteroid therapy with betamethasone (0.1 mg/kg) and an oral antihistamine therapy with oxatomide (1 mg/kg/die) for a week, until resolution. To the best of our knowledge, in the literature, no documented case of reaction to influenza vaccine in maculopapular cutaneous is described. Subsequently, the patient started a background therapy with ketotifen daily (0.05 mg/kg twice daily), a non-competitive histamine-1 antihistamine, and a mast cell stabilizer (dual activity). A non-standardized pharmacological premedication protocol with an H1-receptor antagonist (oxatomide, 0.5 mg/kg) administered 12 hours before the immunizations, and a single dose of betamethasone (0.05 mg/kg) together with another dose of oxatomide (0.5 mg/kg) administered 2 hours before the injections was followed to make it possible for the patient to continue with the scheduled vaccinations. Indeed, no reactions were subsequently reported. Thus, in our experience, a background therapy with ketotifen associated with a premedication protocol made by 2 doses of oxatomide and a single dose of betamethasone was helpful to make possible the execution of the other vaccines. In these children, we suggest considering the idea of taking precautions when vaccination is planned, regardless of the kind of vaccine and if a dose of the same vaccine was previously received. However, a consensus needs to be reached to manage vaccination in children with cutaneous mastocytosis and previous adverse reactions to vaccines.